Restrukturisasi Kredit terhadap Debitur Akibat Wanprestasi Karena Dampak Pandemi Covid-19 - I Made Rai Sukerta; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2021)
The Covid-19 pandemic in Indonesia has not only had an impact on health, the Indonesian economy has also been affected. The banking sector has been affected by this pandemic. Credit restructuring aims to provide relief for debtors in fulfilling their obligations. Then the rules regarding restructuring in the POJK will later become a reference for banks to provide relief for debtors who are affected by covid-19 The Covid-19 pandemic in Indonesia not only has an impact on health, the Indonesian economy is also affected. The banking sector has been affected by this pandemic. Credit restructuring aims to provide relief for debtors in fulfilling their obligations. Then the rules regarding restructuring in the POJK will later become a reference for banks to provide relief for debtors affected by Covid-19. There are several problems faced, namely the form of legal protection for debtors due to default due to the impact of the Covid-19 pandemic and the criteria for debtors who meet the requirements for credit restructuring due to the Covid-19 pandemic. Using normative methods. Benruk legal protection for debtors due to default can apply for credit restructuring in accordance with the POJK. The criteria for debtors who meet the requirements for restructuring are given to debtors if they are really affected by the spread of the corona virus such as a debtor who has a business that is classified as vulnerable to the spread of the corona virus and the debtor's business has decreased income and if indeed the debtor meets these requirements the debtor will meet the restructuring requirements and will be restructured after the debtor is indeed affected by the corona virus